A checklist of millipede genus Hyleoglomeris Verhoeff, 1910 in mainland China, with descriptions of seven new species (Diplopoda, Glomerida, Glomeridae) - Liu, Weixin; Tian, Mingyi (Zootaxa, 2015)
Seven new cavernicolous species of the millipede genus Hyleoglomeris Verhoeff, 1910 are described and illustrated from karsts in southern China: H. grandis sp. n., H. baxian sp. n. from Guangxi Zhuang Autonomous Region; H. rhinoceros sp. n., H. getuhensis sp. n., H. generalis sp. n., H. variabilis sp. n. and H. multistriata sp. n., from Guizhou Province. All of them are presumed troglobites except for H. multistriata sp. n. which is likely to be a troglophile because of its well pigmented body. A distribution map of Hyleoglomeris in Guizhou and Guangxi is also provided.